Project Citizen Model’s Effect on Students’ Learning Interest in Civic Education as an Embodiment of Character Education - Kabatiah, Maryatun; Irwan, Irwan; Firman, Firman (Journal of Moral and Civic Education, 2021)
Civic Education is one of the courses that carry the mission of character education. Compared to other courses, Civic Education course play an important role in teaching character education, meaning that in both courses, character education must be the lecture’s main goal. Civic education is a field of study that carries out the national mission to educate Indonesian people through value-based education. One of the adaptive models in improving the quality of civic education as a manifestation of character building is through Project Citizen. This study aims to determine the effect of project citizen model in the learning interest of students of the Faculty of Teacher Training and Education Sciences (FKIP) University of Jambi (UNJA) in learning civic education as an embodiment of character education. The type of research is an experimental research which is used in Pre-Experimental Design using the Intact Group Comparison draft. In this design, one group of study was divided into a treatment group and a non-treatment group. The population of the study was all of FKIP UNJA students, while the sample was students of class A of the Department of Early Childhood Education (PAUD). The research instrument used was a learning interest questionnaire with questions and statements measured using a Likert scale. The data was then analyzed by the T-test using SPSS 21 software for Windows. Based on the result, it can be concluded that the project citizen model has a significant effect on FKIP UNJA students’ learning interest in learning civic education as an embodiment of character education.